2017
DOI: 10.15356/0435-4281-2017-3-48-59
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Karst and the Neogene Paleo-Belaya Valley Network, Southern Cis-Urals Region

Abstract: Главным фактором, вызвавшим формирование переуглубленной речной сети систем Палео-Волги, Палео-Днепра, Палео-Дона, Палео-Урала и др. палеорек явились тектонические движения земной коры на востоке Русской плиты и Южном Урале в миоцен-плиоценовую эпоху. Они коренным образом трансформировали облик рельефа Южного Предуралья и определили характер и масштабы многих экзогенных процессов. При этом резко усилилась денудационная деятельность подземных вод. В палеодолинах рек Белой, Уфы, Быстрого Таныпа, Демы и др. залег… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Ecological and biological analysis of the flora of petrophytic steppe communities showed that this type of vegetation belongs to the depleted northern petrophytic variant of grass-grass steppes dominated by Hedysarum grandiflorum, Centaurea marschalliana and Euphobia seguieriana, which is close to the previously described by S.M. Yamalov et al [10]: Helictotricho desertori-stipenion rubentis Toman 1969 -steppe communities on stony soils.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Ecological and biological analysis of the flora of petrophytic steppe communities showed that this type of vegetation belongs to the depleted northern petrophytic variant of grass-grass steppes dominated by Hedysarum grandiflorum, Centaurea marschalliana and Euphobia seguieriana, which is close to the previously described by S.M. Yamalov et al [10]: Helictotricho desertori-stipenion rubentis Toman 1969 -steppe communities on stony soils.…”
Section: Resultssupporting
confidence: 84%
“…In the vicinity of the village of Salikhovo, petrophytic steppes have been preserved on the steep slopes of the southern exposure. Sedimentary rocks of different ages -Permian, tertiary and Quaternary systems -take part in the geological structure of the day surface [10].…”
Section: Methodsmentioning
confidence: 99%